Labor Absorption Analysis of Vocational High School Graduates on Employment at Southeast Sulawesi Province - Harafah, La Ode Muhammad; Marlina, Marlina; Rosnawintang, Rosnawintang (International Journal of Management and Education in Human Development, 2025)
The purpose of this study was to find out and analyze the absorption of vocational high school graduates in Southeast Sulawesi Province according to areas of expertise and employment. The object of this research is SMK graduates in Southeast Sulawesi Province. The type of data used in this research is secondary data. Secondary data were obtained from the Southeast Sulawesi BPS, the Southeast Sulawesi Education Office, the Southeast Sulawesi Special Employment Exchange and the Southeast Sulawesi Provincial Labor and Industry Office. Data analysis method used is descriptive analysis. The results of this study indicate that the areas of expertise in Technology and Engineering, Information and Communication Engineering, Business and Management, Tourism, and Arts and Creative Industries are areas of expertise that are mostly absorbed in employment, namely the trade sector, each of which is 4.56% Technology and Engineering, 7.98% Information and Communication Engineering, 9.63% Business and Management, 7.63% Tourism, and 6.8% Industrial and Creative Arts. For the field of expertise in Energy and Mining, much is absorbed in the mining sector, which is 15.72%. Health and Social Worker expertise is mostly absorbed in the Service sector, namely 4.71%. The Agribusiness and Agrotechnology Expertise Fields and the Maritime Expertise Fields were mostly absorbed in the Agriculture sector, respectively 5.18% and 14.35%. On the other hand, the absorption of labor for SMK graduates in Southeast Sulawesi Province is employment with a percentage of 0%.